The Collection of Father Franz Mayr: Zulu Recordings 1908. Sound documents from the phonogrammarchiv of the Austrian Academy of Sciences. The complete historical collections 1899-1950. Series 10. Dietrich Schuller, general editor. Phonogrammarchiv der Osterreichischen Akademie der Wissenschaften OAW CD 25, 2007. ISBN 978-3-7001-3827-3. Two audio CDs, one CD-ROM with 64 page booklet. - Topp Fargion, Janet (International Library of African Music, 2007)
pages: 130-132
Keywords: African Music